Improving radiation hardness in space-based Charge-Coupled Devices: an experimental validation of a new pre-fabrication modelling technique. (1st October 2022) - Parsons, S.; Hall, D.; Buggey, T.; Holland, A.; Verhoeve, P.
Abstract: The soft X-ray imager (SXI) on the SMILE mission uses two large 4510x4510 back illuminated CCD370s to detect X-rays in the 0.2–2 keV range. These devices take heritage from the optical imaging PLATO mission CCD270s and have been optimised for low energy signals by including a parallel supplementary buried channel (SBC) which should reduce the volume of the charge cloud and thereby reduce the number of traps it interacts with as it is transferred through the CCD. The charge transfer performance improvement between the CCD270 and the CCD370 has been simulated using a combination of Silvaco and Matlab models to predict its characteristics pre-fabrication over a 10 2 –10 5 electron signal range. Trap pumping measurements have been taken on both devices to count the number of traps present and hence calculate the mean amount of traps that exist per pixel across the range of signal levels. The trap pumping results are used to calculate a charge transfer performance improvement that shows good agreement with the simulated values, especially in the SXI science band. These results bring added confidence to the early performance modelling of the SMILE SXI instrument and is a good indicator that the simulations are accurate enough to be used to model devices with more advanced geometries such as an SBC and can be used in future CCD missions, where radiation-hardness and hence good charge transfer characteristics are key.